Penggunaan Aplikasi Duolingo dalam Meningkatkan Kosakata Bahasa Inggris Pada Siswa Di Sekolah - Rahmawati, Lela; Anggrawan, Anthony; Hastuti, Hilda; Aprianto, Dedi; Alfilail, Nur (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The aim of community service activities is to provide English language training to students at Madrasah Aliyah Negeri Program Keagamaan (MAN-PK) MAN 2 Mataram. This learning training uses the Duolinglo Application. This training or course involves 2 classes of class X students totaling 50 participants in September and November 2024 at MAN PK MAN 2 Mataram. Each group was asked to use the Duolingo application to integrate English learning. This application is a gamification application, meaning users can learn English like playing games because this application uses audio-visual methods in learning. The methods used in this training are lecture, discussion and direct practice. The result of this service activity is that there is an increase in participants' skills and knowledge in speaking and writing using the Duolingo application. The results of evaluation and monitoring by applying the average post-test score show that the average post-test score (72.18) is greater than the average pretest score (35.78). The implications of community service activities can increase students' knowledge of English at school by using the Duolingo application.